1999
DOI: 10.4269/ajtmh.1999.61.249
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, malaria, and anemia: inverse relationship between nitric oxide production and hemoglobin concentration in asymptomatic, malaria-exposed children.

Abstract: Abstract. The cause of the anemia associated with chronic, intermittent, asymptomatic, low-level parasitemia in children in malaria-endemic endemic areas is not well understood. Nitric oxide (NO) decreases erythropoiesis, and it is likely an important mediator of anemia of chronic disease. Production of NO is decreased in acute uncomplicated and cerebral malaria, but it is increased in asymptomatic Tanzanian children (with or without parasitemia). We hypothesized that chronic overproduction of NO in these asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Since nitric oxide can reduce erythrocyte deformability, 10,11 it could lead to increased red blood cell destruction. 4 This hypothesis is supported by recent findings showing that RNI were negatively correlated with hemoglobin concentrations 12 and were highest in young infants and after 5 years. Thus RNI could possibly contribute to the epidemiological patterns of severe anemia and cerebral malaria.…”
Section: Discussionsupporting
confidence: 77%
“…Since nitric oxide can reduce erythrocyte deformability, 10,11 it could lead to increased red blood cell destruction. 4 This hypothesis is supported by recent findings showing that RNI were negatively correlated with hemoglobin concentrations 12 and were highest in young infants and after 5 years. Thus RNI could possibly contribute to the epidemiological patterns of severe anemia and cerebral malaria.…”
Section: Discussionsupporting
confidence: 77%
“…Further, upregulation of endothelial cell adhesion molecules in response to tumor necrosis factor alpha potentially augments the cytoadherence (22). However, in recent studies, increased NO production has been shown to be beneficial because of its antiparasitic and antidisease effect, although this is controversial, (1). This effect is due to inhibition of the cytoadherence process through downregulation of the expression of ICAM1, VCAM1, and E-selectin, which are involved in cytoadherence and microvascular sequestration of parasitized RBCs (18) and decreased production of tumor necrosis factor by macrophages (9).…”
mentioning
confidence: 99%
“…Anemia is an important complication of malaria both in asymptomatic children and in children with acute febrile episodes (4,24,33). The pathogenesis of malarial anemia is not well understood, but inflammatory cytokines, such as tumor necrosis factor alpha (TNF-␣) and IL-10, are believed to be involved (23,30).…”
mentioning
confidence: 99%